Introduction to the use of belatacept: a fusion protein for the prevention of posttransplant kidney rejection - Ippoliti G (Dove Medical Press, 2012)
Giovanbattista Ippoliti,1,2 Andrea Maria D'Armini,2 Marco Lucioni,3 Mazen Marjieh,1 Mario Viganò21UO Medicina Interna, Policlinico di Monza, Monza, Italy; 2Department of Surgical Sciences, Charles Dubost Transplant Center, Fondazione IRCCS San Matteo Hospital, 3Anatomic Pathology, Foundation IRCCS Policlinico San Matteo, University of Pavia, Pavia, ItalyAbstract: The development of new immunosuppressive drugs for kidney transplantation resulted both in better short-term outcomes and in decreased metabolic, cardiovascular, and nephrotoxicity risk. Belatacept belongs to a new class of immunosuppressive drugs that selectively inhibits T-cell activation by preventing CD28 activation and by binding its ligands B7-1 and B7-2. The result is an inactivation of costimulatory pathways. A comparative analysis of the BENEFIT and BENEFIT-EXT datasets showed belatacept regimens resulted in better cardiovascular and metabolic risk profiles than did cyclosporin A (CsA) regimens: belatacept likewise outperformed CsA in terms of lower blood pressure and serum lipids and less new onset diabetes after transplantation. About 20% of belatacept-treated patients developed adverse effects which included anemia, pyrexia, neutropenia, diarrhea, urinary tract infection, headache, and peripheral edema. At present, belatacept does not seem to predispose patients to a higher rate of infection than CsA maintenance immunosuppression. The risk of posttransplant lymphoproliferative diseases was higher in Epstein–Barr virus (EBV)-seronegative patients than in EBV-seropositive patients, but the risk may be reduced by use of a less intensive regimen and avoidance of EBV-negative patients and of patients whose pretransplant EBV serology is unknown. Belatacept provides a new option for immunosuppressive therapy in kidney transplantation, but needs further evaluation in terms of the late effects that may derive from prolonged blockage of the costimulatory system and the induction of tolerance status.Keywords: costimulation, organ transplantation, belatacept